Hypersonic Weapons and Strategic Stability: How Grave is The Challenge? - Mr. Samran Ali (CISS Insight Journal, 2020)
Hypersonic weapons are becoming a reality with the deployment of Avangard glide vehicle by Russia and the successful testing of such weapons by China and the US. Built to overcome ballistic missile defenses, these weapons are often touted as unstoppable and a possible game-changer. Unlike traditional missiles, hypersonic glide vehicles glide towards their targets giving the defender no time to respond and intercept them. These weapons impact strategic stability by compressing the decision-making time, increasing counterforce temptations due to their precision targeting, and by causing a new arms race. The ability to carry both conventional and nuclear warheads off these weapon can also lead to miscalculation and inadvertent escalation. With weakening arms control and trust deficit at the global level, the global strategic stability would be under stress with the induction of these weapons in nuclear-weapon states’ inventories until some confidence-building measures are adopted. They will continue to challenge the strategic stability even after new systems are developed to counter them.